Prediction of Flow Distribution in Cooled Gas Turbine Blade with Ribs, Pin-Fins and Film Cooling Holes in Leading Edge Passage - Borse, Sachin L. (Journal of Ocean, Mechanical and Aerospace -science and engineering-, 2016)
Modern gas turbine blade is internally cooled to maintain its temperature at safe level. Prediction of mass flow distribution in cooling passage of the turbine blade helps in predicting turbine blade temperature during the design stage. In this current paper, commercial software FLUENT 6.2 is used to predict mass flow distribution in the gas turbine blade cooling passages (like leading edge passage, serpentine passage, trailing edge passage, lateral ejection, tip and film cooling holes) with standard k-e and RNG k-e turbulence models. Model suitable to solve such problem requires huge computational resources. Although present model are not suitable for the problem considered but will help to get approximate results and will also indicate capability of CFD. Results are compared with experimental results. Result showed good agreement of predicted mass flow distribution with experimental results. RNG k-e model shows slight improvement in prediction of the supply pressure over other two models.